Pengaruh Pemberian Kanamisin Oral Sebelum Operasi pada Persiapan Kolon Mekanik Terhadap Konsentrasi Bakteri Kolon dan Rektum - Herizal, Hendra; Usman, Nurhayat; Purnama, Andriana (Ikatan Ahli Bedah Indonesia, 2018)
Background. For decades, ​​colorectal surgical procedures have been associated with high postoperative infections complication. This is expected because of the large number of bacteria in the colon and rectum content. The aim of this study was to investigate wether preoperative oral kanamycin can reduce colonic bacterial concentration, furthermore reduce postoperative infection complication in colorectal malignancy patients who will be performed elective surgical tumor removal. Method. This was an experimental, pre-post test with control group desiagn study, ie groups of patient that prepared with mechanical bowel preparation and administration of oral Kanamycin 3 x 2000 mg a day before the operation day and group of patient that prepared with mechanical bowel preparation only. This study was comparing the concentration of bacteria in the colon and postoperative infection incidence between the two groups. Result. Thirty two patients were randomly assigned to one of two groups, the treatment group and the control group. Obtained equitable distribution of age, sex, tumor location and type of surgery. There was significant bacterial concentration reduction difference between two groups (p = 0.01). There was significant surgical site infection (SSI) incidence difference between two groups, 5 patients (31,3 %) developed an SSI in treatment group and 11 patients (68,8 %) in control group (p=0,03), with OR 0,21 ( CI 95%; 0,046-0,92). Conclusion. Preoperative oral kanamycin could reduce colonic bacteria concentration and SSI incidence in patients with colorectal malignancy who would be performed elective surgical tumor removal. Thus, these methods can be considered its use as a colorectal surgery preparation procedures.